Characterization of home gardens in northern Uruguay and methodology for its diagnosis - Traversa, Ignacio (2013)
An ecological, productive and social  diagnosis of homegardens in Northern Uruguay is displayed in this paper, as well as methodology to achieve it, that could be used in other similar systems.  The fieldwork consisted of interactive surveys to producers and field inventories for gathering information on the social, technical, productive and ecologicalaspects of green orchards. . A map of the orchards was done by using a Geographic Information System (GIS). The homegarden is organic, aligned along the minor and major roads and forms cluster cores at the interface between the urban and peri-urban areas. The prospects of the orchards are limited for socio-cultural reasons. Species biodiversity reached a total amount of 187 and an average of 23 species per orchard. Policies are needed for rescueing inherited knowledge that will keep homegardens alive.